2022
DOI: 10.15845/voices.v22i3.3808
|View full text |Cite
|
Sign up to set email alerts
|

Whose Power, Whose Language? Exploring Issues of Power and Language in Music Therapy

Abstract: This special issue explores the topic of power and language in music therapy in the various ways it manifests within and beyond music therapy. We, the guest editors, are a group of four people at different points of their academic career, some have English as their primary languages and others don’t, we are neurodivergent and neurotypical, living in Norway, Japan, and the US. Our group consists of two music therapists, a musicologist, and an AAC (augmentative and alternative communication) researcher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…All authors are situated in North America, Europe, Australia, and Israel, centring voices within communities of entrenched power. Echoing several of this text's contributors (e.g., Edwards & Baines; Taylor), music therapy pedagogy must continue to reckon with bias that continues to situate knowledge production and expertise within colonising nations (e.g., Metell et al, 2022). Perhaps by no fault of the contributors, this collection perpetuates the hegemonic position of the Global North in music therapy discourse.…”
mentioning
confidence: 99%
“…All authors are situated in North America, Europe, Australia, and Israel, centring voices within communities of entrenched power. Echoing several of this text's contributors (e.g., Edwards & Baines; Taylor), music therapy pedagogy must continue to reckon with bias that continues to situate knowledge production and expertise within colonising nations (e.g., Metell et al, 2022). Perhaps by no fault of the contributors, this collection perpetuates the hegemonic position of the Global North in music therapy discourse.…”
mentioning
confidence: 99%
“…In many cases, I have found that enforcing word choice and grammatical conventions does not actually improve clarity; the author's intent is clear, but presented in a way I had not expected. The editors of the Voices special issue on power and language in music therapy called attention to this, writing that their language was perfectly clear and reflected both their meaning and their collective voice, while sometimes straying outside of grammar conventions idiomatic to Anglo-academic style (Metell et al, 2022).…”
mentioning
confidence: 99%
“…Increasingly within the past several years, music therapists have been challenged to critically engage with their intersectional identities (Baines, 2021;McFerran, 2021) and how certain identities place them within systems of oppression (Metell et al, 2022;Oswanski & Donnenwerth, 2018;Pickard et al, 2020). In addition to this, underrepresented voices from music therapists with minority identities are being brought into fore, revealing how music therapy discourse has historically privileged certain voices over others (Hadley, 2021).…”
Section: Research Question and Aimsmentioning
confidence: 99%